ECCO essential requirements for quality cancer care: Melanoma. (February 2018) - Wouters, Michel W.; Michielin, Olivier; Bastiaannet, Esther; Beishon, Marc; Catalano, Orlando; del Marmol, Veronique; Delgado-Bolton, Roberto; Dendale, Rémi; Trill, Maria Die; Ferrari, Andrea; Forsea, Ana-Maria; Kreckel, Hannelore; et al.
Highlights: ECCO essential requirements for quality cancer care (ERQCC) are position papers on delivering high-quality care. Each paper focuses on a cancer type, in this case melanoma. Advanced melanoma is complex to stage and treat, with many new options. High-quality care can only be a carried out in specialised units or centres. The essential, multidisciplinary details for such centres are set out by the ERQCC expert group. Abstract: Background: ECCO essential requirements for quality cancer care (ERQCC) are explanations and descriptions of challenges, organisation and actions that are necessary to give high-quality care to patients who have a specific type of cancer. They are written by European experts representing all disciplines involved in cancer care. ERQCC papers give oncology teams, patients, policymakers and managers an overview of the elements needed in any healthcare system to provide high quality of care throughout the patient journey. References are made to clinical guidelines and other resources where appropriate, and the focus is on care in Europe. Melanoma: essential requirements for quality care: Melanoma, the most-deadly skin cancer, is rising in incidence among fair-skinned people in Europe. Increasing complexity of care for advanced disease in clinical areas such as staging and new therapies requires attention to a number of challenges and inequalities in a diverse patient group. Care for advanced melanoma must only be carried out in, or in collaboration with, specialist melanoma centres which have both a core multidisciplinary team and an extended team of allied professionals, and which are subject to quality and audit procedures. Access to such units is far from universal in all European countries. It is essential that, to meet European aspirations for high-quality comprehensive cancer control, healthcare organisations implement the requirements in this paper, paying particular attention to multidisciplinarity and patient-centred pathways from diagnosis to treatment and follow-up, to improve survival and quality of life for patients. Conclusion: Taken together, the information presented in this paper provides a comprehensive description of the essential requirements for establishing a high-quality service for melanoma. The ERQCC expert group is aware that it is not possible to propose a 'one size fits all' system for all countries, but urges that access to multidisciplinary teams and specialised treatments is guaranteed to all patients with melanoma.